d-Cysteine-Induced Rapid Root Abscission in the Water Fern Azolla Pinnata: Implications for the Linkage between d-Amino Acid and Reactive Sulfur Species (RSS) in Plant Environmental Responses - Hideo Yamasaki; Masahiro P. Ogura; Katsumi A. Kingjoe; Michael F. Cohen (MDPI AG, 2019)
Reactive Oxygen Species (ROS) and Reactive Nitrogen Species (RNS) have been proposed as universal signaling molecules in plant stress responses. There are a growing number of studies suggesting that hydrogen sulfide (H2S) or Reactive Sulfur Species (RSS) are also involved in plant abiotic as well as biotic stress responses. However, it is still a matter of debate as to how plants utilize those RSS in their signaling cascades. Here, we demonstrate that d-cysteine is a novel candidate for bridging our gap in understanding. In the genus of the tiny water-floating fern Azolla, a rapid root abscission occurs in response to a wide variety of environmental stimuli as well as chemical inducers. We tested five H2S chemical donors, Na2S, GYY4137, 5a, 8l, and 8o, and found that 5a showed a significant abscission activity. Root abscission also occurred with the polysulfides Na2S2, Na2S3, and Na2S4. Rapid root abscission comparable to other known chemical inducers was observed in the presence of d-cysteine, whereas l-cysteine showed no effect. We suggest that d-cysteine is a physiologically relevant substrate to induce root abscission in the water fern Azolla.